Theoria – praxis – poiesis as a challenge and perspective of methodological critique in pedagogy - Nowak, Marian (Methodological critique in the practice of knowledge creation, 2019)
Considering the theme of the 7th Seminar on Pedagogical Methodology, the chapter focuses on issues related to three categories (theoria, praxis, and poiesis) and the values appropriately assigned to them (truth, goodness, and beauty). By characterizing the role of these categories as the criteria of critical analysis applied to pedagogical knowledge outcomes, this chapter points to their continuing relevance and the special meaning of the value of truth. Truth is an important criterion for critical analysis, as well as the goal of human cognition, an initial and fundamental value, checking the value of all other human personal activities. It constitutes a human individuality composed of three types of truths 1) the truth, which exists (TRUTH); 2) the truth, which becomes (GOOD); and 3) the truth, which is to be (BEAUTY). These are the three spheres of human existence in which the types occur and, at the same time, they can be a criterion of methodological critique used in creating and analysing pedagogical knowledge, indicating human potentialities, which are understood as the things possible to lift humans to the highest possible level (the optimum potentiae) as the top capabilities of a human being. In the Christian context, one can think of some state of a perfect virtue that ‘makes both the having person and his work good’ (Krąpiec, 1990, p. 41).